THE TRAINING TO IMPROVE SPEED YOSHINKAN AIKIDO - Vasile BOGDAN; Alexandra POP; Petre-Ion BARBOŞ (Cluj University Press, 2015)
Introduction. Aikido, "the way of harmony and love, containing techniques for developing balance, coordination body (joint techniques, throwing, pivot)". It is approached at early ages, being a branch of sport much favored by children at young ages 6-10 years. This sub-branch of martial arts, due to exoticism, of how it is perceived by the little children produce emulation attracts to practice of a lots of children. On the on the one hand because of the "mysteries" that accompany this sport, on the other hand due to the instructive accompanying it. Among the many branches of martial arts, where some have the tendency more strongly to only focus on technical training, ignoring physical training, other martial arts ignore even preparing locomotor system, to practice safely this art, some even preparing musculoskeletal the practice safely this art. Current Aikido (Aikido Yoshinkan and Takemutsu) maintained in the training program and attaches the utmost importance of physical training: by approaching varied means of physical training for all age levels. Even for young children, a fact demonstrated in the pilot experiment conducted in 2012, the first program launched in Romania in the private school "Happy Kids", today "Transylvania College, Cambridge International School-Cluj". This article proposes practitioners a set of athletics exercises in order to strengthen speed, with its forms of expression. By practicing these means of athletic, 2-3 times a week, can obtain high values of this quality (if there is genetic determinations), while in generally, give positive results in improving the biometric qualities, but also the correction of some posts balance or even fighting techniques. Antrenamentul pentru perfecționarea vitezei în Yoshinkan aikido. Yoshinkan Aikido este o ramură a aikido-ului care urmărește, pe lângă pregătirea tehnică, și perfecționarea calităților motrice de bază și specifice. Scopul acestui studiu a fost de a stabilii raportul de performanță între elevii care practică sistematic forme de pregătire specifice atletismului (alergare de viteză) și cei care practică doar tehnicile aikido-ului. Materiale și metode. 20 de elevi voluntari din fosta școala "Happy Kids", astăzi "Transylvania College, Cambridge International School-Cluj". Au fost executate măsurători antropometrice (greutate, înălțime). Toți subiecții au efectuat două teste: 1. Testul "Transfer" 2. Testul "Bip" în urma căruia s-a constatat că viteza era cuprinsă între 18 și 48 de secunde la primul test, în timp ce la al doilea test fiind de 1,3 și 3,6 secunde, la grupul de control. La testul final, grupa de control a obținut un rezultat superior, înregistrând chiar și 10 secunde mai puțin decât la prima testare. Concluzii: creșterea vitezei de reacție, deosebit de importantă în artele marțiale a fost vizibil superioară odată cu introducerea alergării de viteză din atletism. Totuși, un punct negativ al acestei cercetări este că cercetarea a fost realizată pentru o perioadă scurtă de timp (3 luni) și nu știm în ce măsură aceste îmbunătățiri ale vitezei se pot menține în timp. De asemenea ar fi important de cercetat efectul antrenamentelor de acest tip și la adulți, unde parametrii ar trebui să fie diferiți. Cuvinte cheie: Viteză, forță, rezistență, aikido, Saito sensei, Kata, Koshi-nage, disciplină, echilibru, coordonare.